KEDUDUKAN PELAKU TINDAK PIDANA PENCUCIAN UANG YANG DAPAT BERTINDAK SEBAGAI WHISTLEBLOWER & JUSTICE COLLABORATOR DALAM PROSES PENEGAKAN HUKUM - Armia Pahmi; Bismar Nasution; Mahmud Mulyadi; Suhaidi Suhaidi (Universitas Sumatera Utara, 2019)
Abstract : The position of justice collaborator and whistleblower as a subject and witnes of money loundrey of course could help Law Enforcement Agencies to come criminal act that had relation to money loundrey. The problem of the study of this research were how the background of justice collaborator and whistleblower growed in Indonesia was, how the regulation of justice collaborator and whistleblower in Indonesia was and how the position of criminal act in money loundrey that could become as justice collaborator and whistleblower. The method of this research used Normatif Law Research which was pointed to the law norms that had in legislation and court judgement. The backround of justice collaborator and whistleblower in Indonesia was begund from whistle blower in England if there was a criminal. Meanwhile the regulation of justice collaborator and whistleblower could be seen in Supreme Court Circular Letter No. Year 2011 about whistleblower and justice colabolator in particular case. Constitution No. 13 year 2006 about victim and witness and changing namely Constitution No. 31 Year 2014. Whistleblower was a witness informant while justice colaborator was a witness and a person who did criminal in money loundrey. KeyWords : position of whistleblower; justice collabolator; and money laundry.